Correlation of Glasgow coma scale (GCS) score and neuroimaging radiological interpretation system (NIRIS) in patients with traumatic brain injury (TBI) - Niaz, Murk; Khokhar, Amina Shamshad; Muhammad Faaiq Ali,; Irfan Ali Shah,; Muhammad Asim Khan Rehmani,; Talha Bhatti, (Journal of the Pakistan Medical Association, 2025)
Objective: To determine the correlation of the Glasgow Coma Scale score and different Neuroimaging Radiological Interpretation System categories in patients with traumatic brain injury. Method: The prospective observational study was conducted at the Shaheed Mohtarma Benazir Bhutto Institute of Trauma, Karachi, from July to December 2023, and comprised patients aged at least 18 years with documented traumatic brain injury. The patient underwent assessment in the emergency department. The mechanism of injury, and Glasgow Coma Scale score at the time of hospital arrival were noted. A non-contrast head computed tomography scan was done to acquire images of sufficient quality for Neuroimaging Radiological Interpretation System classification. Data was analysed using SPSS 23. Results: Of the 388 patients with mean age 33.44±18.51 years, 319(82.2%) were males and 69(17.8%) were females. Road traffic accidents accounted for 283(72.9%) cases. Glasgow Coma Scale-based severity classification revealed mild traumatic brain injury in 185(47.7%), moderate in 100(25.8%) and severe in 103(26.5%) patients. Neuroimaging Radiological Interpretation System category distribution showed category 2 being the most frequent 165(42.5%), while category 0 was least common 5(1.3%). There was a strong negative correlation between Glasgow Coma Scale scores and Neuroimaging Radiological Interpretation System categories (p=0.001), with the coefficient of determination indicating that 27.4% of Glasgow Coma Scale score variance was explained by Neuroimaging Radiological Interpretation System classification. Conclusion: There was a negative correlation between Neuroimaging Radiological Interpretation System category and Glasgow Coma Scale score in patients with traumatic brain injury.